Resuscitative endovascular balloon occlusion of the aorta (REBOA): a scoping review protocol concerning indications—advantages and challenges of implementation in traumatic non-compressible torso haemorrhage. Issue 2 (3rd February 2019) - Bekdache, Omar; Paradis, Tiffany; Shen, Yu Bai He; Elbahrawy, Aly; Grushka, Jeremy; Deckelbaum, Dan L; Khwaja, Kosar; Fata, Paola; Razek, Tarek; Beckett, Andrew
Abstract : Introduction: Haemorrhage remains the leading cause of preventable death in trauma. Damage control measures applied to patients in extremis in order to control exsanguinating bleeding from non-compressible torso injuries use different techniques to limit blood flow from the aorta to the rest of the body. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is regaining momentum recently as an adjunct measure that can provide the same results using less invasive approaches. This scoping review aims to provide a comprehensive understanding of the existing literature on REBOA. The objective is to analyse evidence and non-evidence-based medical reports and to describe current gaps in the literature about the best indication and implementation strategies for REBOA. Methods and analysis: Using the five-stage framework of Arksey and O'Malley's scoping review methodology as a guide, we will perform a systematic search in the following databases: MEDLINE, EMBASE, BIOSIS, COCHRANE CENTRAL, PUBMED and SCOPUS from the earliest available publications. The aim is to identify diverse studies related to the topic of REBOA. For a comprehensive search, we will explore organisational websites, key journals and hand-search reference lists of key studies. Data will be charted and sorted using a descriptive analytical approach. Ethics and dissemination: Ethics approval is not necessary as the data are collected from publicly available sources and there will be no consultative phase. The results will be disseminated through presentations at local, national, clinical and medical education conferences and through publication in a peer-reviewed journal.